2019
DOI: 10.17159/2312-3621/2019/v32n1a7
|View full text |Cite
|
Sign up to set email alerts
|

YHWH and Israel in terms of the Concept of Life in Deuteronomy

Abstract: References to the concept of "life" (the root ‫)חיה‬ are found throughout the book of Deuteronomy. Yet very few surveys have been done on the concept of life in Deuteronomy. This article contributes to the discussion by giving a survey of the different ways in which the concept of life is employed in the book. The results of this survey are used to give an overview of this concept from a theological point of view by determining what Deuteronomy as a whole says about YHWH and Israel in terms of the concept of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In another article, I give a survey of the different ways in which the concept of life ‫]חיה[‬ is employed in Deuteronomy (Coetsee 2019). The study finds that the root ‫חיה‬ is found 39 times in the book of Deuteronomy, consisting of the verb ‫יה‬ ָ ‫ח‬ ָ (18x; 'live'), the adjective ‫חי‬ ַ (8x; 'alive') and the nouns ‫ּים‬ ִ ‫ַי‬ ‫ח‬ (12x; 'life') and ‫יה‬ ָ ‫ח‬ ָ (1x; 'living thing' or 'wild animal').…”
Section: The Multifaceted Concept Of 'Life' In Deuteronomymentioning
confidence: 99%
“…In another article, I give a survey of the different ways in which the concept of life ‫]חיה[‬ is employed in Deuteronomy (Coetsee 2019). The study finds that the root ‫חיה‬ is found 39 times in the book of Deuteronomy, consisting of the verb ‫יה‬ ָ ‫ח‬ ָ (18x; 'live'), the adjective ‫חי‬ ַ (8x; 'alive') and the nouns ‫ּים‬ ִ ‫ַי‬ ‫ח‬ (12x; 'life') and ‫יה‬ ָ ‫ח‬ ָ (1x; 'living thing' or 'wild animal').…”
Section: The Multifaceted Concept Of 'Life' In Deuteronomymentioning
confidence: 99%